2019
DOI: 10.1136/jclinpath-2019-206128
|View full text |Cite
|
Sign up to set email alerts
|

Somatic deletion ofKDM1A/LSD1gene is associated to advanced colorectal cancer stages

Abstract: AimsKDM1A/LSD1 and ZNF217 are involved in a protein complex that participates in transcriptional regulation. ZNF217 has been analysed in numerous cancers and its amplification has been associated with advanced stages of disease; however, a similar role for KDM1A/LSD1 has not been uncovered. In this study, we estimated the number of KDM1A/LSD1 and ZNF217 gene cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…KDM1A was overexpressed in various malignant tumors, including cervical cancer ( 38 ), esophageal cancer ( 39 ), ovarian cancer ( 40 ), and GC ( 41 ). The elevated KDM1A level was also related to tumor stage, histological grade, and lymph node metastasis ( 42 ). Additionally, KDM1A is a regulator of embryonic stem cells and can affect the self-renewal and differentiation of human embryonic stem cells ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…KDM1A was overexpressed in various malignant tumors, including cervical cancer ( 38 ), esophageal cancer ( 39 ), ovarian cancer ( 40 ), and GC ( 41 ). The elevated KDM1A level was also related to tumor stage, histological grade, and lymph node metastasis ( 42 ). Additionally, KDM1A is a regulator of embryonic stem cells and can affect the self-renewal and differentiation of human embryonic stem cells ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the 12 functional genes have been connected with COAD or other diseases according to the existing research. For example, TPM2 was reported to be in implicated in CRC [ 60 ]; STMN2 might be involved in beta-catenin/TCF-mediated carcinogenesis in human hepatoma cells [ 61 ]; CHMP4C was identified as a novel molecular target gene for ovarian cancer [ 62 ]; GRIA3 may act as a mediator of tumor progression in pancreatic cancer [ 63 ]; WDR1 was reported as a therapeutic target in lung cancer [ 64 ]; CPT2 was identified as a potential diagnostic biomarker of colon cancer [ 65 ]; Somatic deletion of KDM1A plays role in advanced colorectal cancer stages [ 66 ]; NFE2L1 , also called Nrf1, was found to be associated to high-risk diffuse large B cell lymphoma [ 67 ]; Gatza et al reported that TGFBR3 promotes colon cancer progression [ 68 ]; FGFR2 was shown to promote gastric cancer progression [ 69 ]. Therefore, the 12 functional genes probably play important roles in COAD and could be the potential prognosis biomarkers for COAD.…”
Section: Discussionmentioning
confidence: 99%
“…These results shed light on the role of DACH1 and introduce a possible prognostic marker and therapeutic goal for CRC patients [ 127 ]. Furthermore, lysine-specific demethylase 1 (LSD1), a well-known chromatin-modifying enzyme, is overexpressed in CRC and associated with proliferation and migration mainly by transduction of the phosphoinositide 3-kinase (PI3K)/Akt axis [ 128 ]. In this regard, Miller et al.…”
Section: Crispr/cas9 In Cancersmentioning
confidence: 99%